The Role of the P1BS Element Containing Promoter-Driven Genes in Pi Transport and Homeostasis in Plants - Sobkowiak, Lukasz; Bielewicz, Dawid; Małecka, Ewelina; Jakobsen, Iver; Albrechtsen, Merete; Szweykowska-Kulinska, Zofia; Pacak, Andrzej M. (Frontiers in Plant Science, 2012)
Inorganic phosphate (Pi) is an easily accessible form of phosphorus for plants. Plant Pi uptake is usually limited by slow Pi diffusion through the soil which adsorps the Pi quite strong. That is why plants have developed mechanisms to increase Pi availability. There are abiotic (phosphate level) and biotic (mycorrhiza) factors regulating the expression of Pi-responsive genes. Transcription factors binding to the promoters of Pi-responsive genes activate different pathways of Pi transport, distribution and homeostasis maintenance. Pi metabolism involves proteins, as well as microRNAs and other noncoding RNAs.